Intelligent change the science behind digital transformations - Budzier, Alexander 1979-; Gottschalck, Thomas; Thuesen, Kim Bjørn; Lanng, Astrid (Wiley, 2025)
"In Intelligent Change: The Science Behind Digital Transformations, a team of renowned project management and digital transformation experts delivers a how-to manual for expansive technology change initiatives at firms of all types and sizes. The authors rely on a systematic review of over 1800 publications, interviews with 160 top-level managers, and fieldwork studying 150 digital transformation projects to bring you research- and data-backed strategies you can implement at your own organization to ensure your own project provides business value"--
Includes index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Business -- Technological innovations; Project management; Technological innovations -- Finance; Affaires; Innovations; Gestion de projet; Innovations; Finances; Management; Strategic Planning; BUSINESS & ECONOMICS; Leadership